P702 Clinical and biomarker remission is maintained after switch from monthly dosed intravenous to subcutaneous maintenance treatment with vedolizumab in Inflammatory Bowel Disease. (30th January 2023) - Pintar, S; Hanžel, J; Smrekar, N; Koželj, M; Drobne, D; Kurent, T; Štabuc, B; Novak, G
Abstract: Background: Background: Subcutaneous (SC) formulation of vedolizumab (VDZ), a gut selective integrin antagonist used for treatment of inflammatory bowel disease (IBD), has proven effective and safe in clinical trials after intravenous (IV) induction. However, it is not clear if patients can be effectively switched from IV maintenance treatment to SC. We aimed to assess real-world efficacy of switch from IV to SC formulation and to investigate if baseline maintenance regimen (every 8 weeks (q8) versus every 4 weeks(q4)) impacts outcome after switch. Methods: Methods: In this observational study at a tertiary referral centre, we enrolled 126 prospectively followed consecutive adult patients with IBD who were switched to SC VDZ maintenance treatment. We included patients after IV induction (2 or 3 infusions) and patients who switched from IV maintenance treatment q8 and q4. SC VDZ dosing was 108 mg every 2 weeks regardless of the previous IV regimen. Clinical (Harvey Bradshaw index (HBI) for Crohn's disease (CD) and partial Mayo score (pMayo) for ulcerative colitis (UC)) and biochemical disease activity (CRP, fecal calprotectin (FC)) were assessed at the time of switch and at first and second follow-up. HBI<5 and pMayo<2 were considered clinical remission. CRP <5mg/L and FC<150mg/kg were considered biomarker remission. Results: Results: In total 126 patients (40% CD, 60% UC) were switched to SC vedolizumab. Demographics and baseline characteristics are presented in Table 1. Median time to 1 st follow up (FU) was 14, 5 weeks (IQR 12-26) and median time to 2 nd FU was 40 (IQR 36-52) weeks. From all patients, 8/126 (6%) discontinued SC VDZ treatment, 5 of them due to endoscopically active disease (2 in IV induction group, 3 in q4 group), 1 had dysplasia and required surgery (IV induction group), two others (both q8 group) discontinued on their wish. In patients who continued SC treatment clinical and biomarker remission appears to be maintained at 1 st and 2 nd FU. Clinical and biomarker outcomes are presented in Table 1. Vedolizumab concentrations were 16.9, 24.6 and 13.0 at baseline, 27.0, 25.3 and 25.2 at 1 st FU and 25.5, 34.6 and 22.1 at 2 nd FU in the q8, q4 and IV induction group, respectively. Conclusion: Conclusion: The results of this real-world study suggest maintenance of clinical and biomarker remission in patients switched from IV to SC vedolizumab. Baseline vedolizumab dosing regimen (every 4 weeks versus every 8 weeks) did not have an impact on outcomes.